Answer:
(x+4)(3x^2 + 2)
Step-by-step explanation:
3x^3+12x^2+2x+8
3x^2(x + 4) + 2(x + 4)
(x+4)(3x^2 + 2)
If a point is translated right and up, then the image of the point should be to the right and up from the original point, aka the preimage.
Let's go through the choices.
A. Point D could be the image of B.
D is up and to the right of B, so yes. Select choice A
B. Point C could be the image of A.
C is below A, so no
C. Point E could be the image of C.
E is up and to the right from C so yes, Select choice C
D. Point D could be the image of A.
D is down and to the right of A so no.
E. Point E could be the image of B.
E is up and to the right of B so yes. Select choice E
F. Point C could be the image of E.
No C is down and to the left of E.
Answers: A C E
The point-slope form of a line is:
y-y1=m(x-x1), where m=slope and (x1,y1) is any point on the line
First we need to find the slope, which is (y2-y1)/(x2-x1)
m=(4--1)/(8-2)
m=5/6 and we can use either point, I'll use (8,4)
y-4=(5/6)(x-8)
That is your equation in point-slope form.
Now the standard equation of a line is ax+by=c
y-4=(5/6)(x-8) we can perform the indicated multiplication on the right side
y-4=(5x-40)/6 multiply both sides by 6
6y-24=5x-40 add 24 to both sides
6y=5x-16 subtract 5x from both sides
-5x+6y=-16 and by convention, the standard equation of a line should be expressed with a positive coefficient for x, so multiply both sides by -1
5x-6y=16
The first poster is not an accurate representation of the painting, but the second poster is an accurate representation because the ratio between the first and original lengths did not equal the ratio between the first and original widths but the second poster's ratios were equal.
The function can be solved as follows:
- f(6 + 4) = 25
- f(6) - f(4) = 20
- f(6 - 4) = 1
- f(6) - f(4) = 6
- f(6) . f(4) = 91
<h3>How to solve function?</h3>
f(x) = 3x - 5
Therefore, the function can be solved as follows:
f(6 + 4) = f(10) = 3(10) - 5 = 25
f(6) + f(4) = 3(6) - 5 + (3(4) - 5)
f(6) - f(4) = 13 + 7
f(6) - f(4) = 20
f(6 - 4) = f(2) = 3(2) - 5 = 6 - 5 = 1
f(6) - f(4) = 3(6) - 5 - (3(4) - 5)
f(6) - f(4) = 18 - 5 - (12 - 5)
f(6) - f(4) = 13 - 7
f(6) - f(4) = 6
f(6.4) = f(24) = 3(24) - 5 = 72 - 5 = 67
f(6) . f(4) = (3(6) - 5 ) (3(4) - 5)
f(6) . f(4) = (18 - 5)(12 - 5)
f(6) . f(4) = (13)(7) = 91
learn more on function here: brainly.com/question/9390144
#SPJ1